INVESTIGATING TOURISTS’ INTENTION TO REVISIT A BATIK- BASED TOURISM DESTINATION: HOW DOES THE ROLE OF DESTINATION IMAGE? - Elena Puspita Candra; Usep Suhud; Ika Febrilia (Universitas Terbuka, 2020)
This study aims to examine the factors that influence revisit intention (z) such as destination image (x1) and perceived value (x2) as independent variable, tourist satisfaction (y1) and memorable tourism experience (y2) as intervening variable. Data collection is done with survey methods, and the instruments used were questionnaires. The number of samples used in this study were 259 respondents in the form of tourists, both the archipelago and foreign tourists who traveled and shopped in Batik Trusmi Area, Cirebon. Data analysis uses SPSS version 22 and AMOS version 22 techniques to process the research data. Then, the study revealed that destination image and perceived value positively and significantly influence satisfaction. Destination image and perceived value affect the memorable tourism, satisfaction and memorable tourism have a positive and significant effect on revisit intention.